Blended Learning Strategy in the New Normal Era (TPACK Competency Study) - Endah Juwandani; Aldina Siti Nur Aliyah; Citra Sukma Melati; Ratnawati Susanto (Pedagonal : Jurnal Ilmiah Pendidikan, 2022)
This article discusses about Blended Learning Strategy in the New Normal Era using the TPACK Competency Study. The TPACK approach is an approach that was developed from the Pedagogy Content Knowledge (PCK) approach which integrates technology and learning. The purpose of this study was to get an idea of the teacher's strategy at SDN Kapuk Muara 03 in preparing blended learning in the new normal era. This research is a case study with a qualitative approach. Data collection techniques using observation and interviews. The focus of this research object is one of the teachers at SDN Kapuk Muara 03. The results show that the preparation of blended learning in the new normal era has been designed quite well by the teacher. The strategy is carried out with planned steps and stages: (1) planning and arranging face-to-face and online schedules in turns with the aim of avoid crowds, (2) preparing facilities and infrastructure related to health protocols, (3) carry out Covid-19 prevention conditioning through 5 M;  wear masks, wash hands with soap and running water, maintain distance, stay away from crowds, and limit mobilization and interaction, (4) conduct online and offline learning education for students and parents, (5) apply technological competence, pedagogical and knowledge content in blended learning, (6) conduct learning that leads to 4Cs, (7) apply self-feedback evaluation as understanding students on their learning outcomes.